Regulation of Nanomaterials in the EU: Proposed Measures to Fill in the Gap. (June 2014) - Azoulay, David; Buonsante, Vito
Abstract : This report discusses a proposal fromthe Center for International Environmental Law(CIEL), ClientEarth and Friends of the Earth Germany (Bund) on the regulation of nanomaterials in the European Union. It discusses in particular, the proposal for a horizontal regulation on nanomaterials (also referred to as a nano-patch for existing legislation) that would fill in the regulatory gap on nanomaterials. The proposal goes beyond a review of the REACH text and encompasses all EU legislation relevant to nanomaterials. The proposed instrument would amend the REACH text with delimitation in scope to all areas relevant to nanomaterials (on the model of Regulation 1272/2008 on the classification, labelling and packaging of chemicals). The main aim of the regulation is to ensure that hazard, risk and exposure assessments for all forms and uses of such materials are adequately carried out and taken into consideration.